2014
DOI: 10.1007/978-1-4614-3209-8_26
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Monocytes and Macrophages in Age-Related Macular Degeneration

Abstract: White blood cells, particularly monocytes and their descendants, macrophages, have been implicated in age-related macular degeneration (AMD) pathology. In this minireview, we describe the current knowledge of monocyte and macrophage involvement in AMD. Chemokine receptors present on these cells such as CCR1, CCR2, and CX3CR1, and their roles in monocyte/macrophage recruitment to sites of injury and inflammation in the context of AMD will be reviewed. Mice models for perturbation of chemokine receptors that rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
0
15
0
1
Order By: Relevance
“…We cross‐validated the RNA‐seq data from each functional category in AhR −/− and wt mouse RPE‐choroid samples using qPCR (Figure B); primers are listed in Table S3 (see supplementary material). We observed down‐regulation of Gpr124 , a regulator of angiogenesis also known as tumour endothelial factor 5 , down‐regulation of the ECM gene collagen type V α 1 ( Col5a1 ) and up‐regulation of the inflammatory gene chemokine (C–C motif) receptor 1 ( Ccr1 ) . These genes displayed a significant fold change, the direction and magnitude of which was consistent with the RNA‐seq analysis.…”
Section: Resultsmentioning
confidence: 86%
“…We cross‐validated the RNA‐seq data from each functional category in AhR −/− and wt mouse RPE‐choroid samples using qPCR (Figure B); primers are listed in Table S3 (see supplementary material). We observed down‐regulation of Gpr124 , a regulator of angiogenesis also known as tumour endothelial factor 5 , down‐regulation of the ECM gene collagen type V α 1 ( Col5a1 ) and up‐regulation of the inflammatory gene chemokine (C–C motif) receptor 1 ( Ccr1 ) . These genes displayed a significant fold change, the direction and magnitude of which was consistent with the RNA‐seq analysis.…”
Section: Resultsmentioning
confidence: 86%
“…Together, these results demonstrated that AMD patients presented an enrichment of Th1 and Th17 cells in PBMCs. [19]. Prior to the induction of retinal lesion, macrophages enriched in the M1 type were found to infiltrate the interphotoreceptor matrix in mice, while in CCR2-deficient mice with no infiltration of macrophages, no retinal lesion was observed [20].…”
Section: Ifn-γ + Th1 Cells and Il-17 + Th17 Cells Were Upregulated Inmentioning
confidence: 99%
“…While a wide body of knowledge exists on the role of macrophages in disease of the outer retina 18,19 and experimental data are available, 20 little is known about the dynamics of macrophages during RVO, a chronic disease of the inner retina characterized by hypoxia. We and others have previously described a mouse model of experimental branch retinal vein occlusion (BRVO).…”
mentioning
confidence: 99%